Ecological changes during crisis period. Issue 1 (January 2021) - Kyzym, M; Gavkalova, N; Lola, Y; Prokopovych, S; Jain, Pradeep
Abstract: The article examines the change of the level of air pollution in world's countries (ecological changes). We verified two hypotheses. It can be caused by an increase in the level of development of countries accompanied by a change in the level of air pollution and the countries with different rates of economic growth may observe different rates of air pollution reduction in the post-crisis period. To test the hypotheses, hierarchical agglomerative and iterative methods of cluster analysis, and econometric models were used. The annual percentage growth rate of the GDP per capita and percentage of population exposed to ambient concentrations of PM2.5 for 101 countries for 2008-2017 were considered as the research information base. The results showed both significant positive and negative effects of increasing level of economic development and air pollution of the countries with a time lag in one-two year. In addition, the results of an econometric analysis show that there are different dynamics of air pollution level for countries with high, medium and low economic growth rates. The results can be of value for the formation and adaptation of the environmental strategies.